2022
DOI: 10.3390/jcm11195803
|View full text |Cite
|
Sign up to set email alerts
|

Transient Global Amnesia (TGA): Sex-Specific Differences in Blood Pressure and Cerebral Microangiopathy in Patients with TGA

Abstract: Transient global amnesia (TGA) is defined by an acute memory disturbance of unclear aetiology for a period of less than 24 h. Observed psychological, neuroanatomical and hormonal differences between the sexes in episodic memory suggest sex-specific differences in memory disorders such as TGA. The aim of this study was to determine sex-specific differences in cardiovascular risk profiles, recurrences and magnetic resonance imaging (MRI). In total, 372 hospitalised TGA patients between 01/2011 and 10/2021 were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…Before final disposition, the patient did admit that she had recently been traveling for various job conferences and was feeling worn down due to occupational stress. Past studies have also revealed differences between the male and female sex in terms of the incidence and development of TGA (Rogalewski et al, 2022) [9]. Furthermore, the researchers discovered a stronger female predominance while also revealing that more emotional triggers were seen in female patients, but more physiologic triggers and chronic hypertension were seen in male patients.…”
Section: Discussionmentioning
confidence: 95%
“…Before final disposition, the patient did admit that she had recently been traveling for various job conferences and was feeling worn down due to occupational stress. Past studies have also revealed differences between the male and female sex in terms of the incidence and development of TGA (Rogalewski et al, 2022) [9]. Furthermore, the researchers discovered a stronger female predominance while also revealing that more emotional triggers were seen in female patients, but more physiologic triggers and chronic hypertension were seen in male patients.…”
Section: Discussionmentioning
confidence: 95%